Comparing visible and less visible costs of the Habitats Directive: The case of hamster conservation in Germany - Florian V. Eppink; Frank Wätzold (Helmholtz-Zentrum für Umweltforschung (UFZ), 2007)
The EU Habitats Directive provides in Annexes II and IV a list of species needing to be conserved. Member States have implemented a variety of conservation measures in response to this obligation. These measures include the rejection, modification or delay of land development plans, payments for landowners to perform conservation measures and management actions such as breeding programmes. The costs of the various conservation measures are not always apparent. There may be an underestimation of the resulting costs when land development plans are altered, because there is no visible flow of financial resources. Such a biased perception may result in selecting conservation measures with high but less visible costs, whereas conservation measures with low but more visible costs are neglected. The purpose of this paper is to contribute to avoiding a biased selection of conservation measures by presenting a framework which captures a broad variety of costs relevant to the conservation of species protected by the Habitats Directive. We also demonstrate the relevance of a biased selection of conservation measures by using the framework to empirically estimate the costs of protecting the common hamster (Cricetus cricetus) in the region of Mannheim, Germany. We find that the less visible costs of changes in development plans are significantly higher than the more visible costs of payments to landowners and management actions. This result suggests that measures with visible costs should be given more attention in the future.
Keywords: 330; Common hamster; Cost assessment; Cost-effectiveness; EU Habitats Directive; Land use; Spatial planning; Species conservation